Using Pixton to Improve Students’ Creativity on Creating Dialogue - Nisrina Nurhaliza; Rana Khairunnisa (Proceedings Series on Physical & Formal Sciences, 2022)
Pixton is an interesting comic creation site that can for the teacher and the students on creating dialogue during the teaching and learning process. This research was aimed at revealing the use of Pixton to improve students’ creativity on creating dialogue. This is a descriptive study in which the data from the field was analyzed descriptively. One teacher and three students participated in this research. To investigate the use of Pixton whether it affected the positive roles or not, observation and interview were used. The observation showed that the teacher gave the procedure in using Pixton clearly and the students understand it easily. On the other hand, the interview provided a result that a teacher and a student some ideas about Pixton such as can improve the creativity, easy to access, enjoyable application, etc. Furthermore, there are some, using Pixton also as a way to create a dialogue efficiently and effectively.